The Impact of Electronic Medical Record Implementation on Labor Cost and Productivity at an Outpatient Orthopaedic Clinic. (19th September 2018) - Scott, Daniel J.; Labro, Eva; Penrose, Colin T.; Bolognesi, Michael P.; Wellman, Samuel S.; Mather, Richard C.
Abstract : Background: Widespread adoption of electronic medical record (EMR) systems is increasing. EMR implementation can be costly and typically requires workflow redesign. To our knowledge, no studies to date have examined the impact of EMR implementation using advanced cost accounting methods or the impact of its implementation on orthopaedic surgeons in an outpatient setting. Methods: Time-driven activity-based costing (TD-ABC) was used to evaluate the effect of EMR implementation in an outpatient adult reconstruction clinic. One hundred and forty-three patients were prospectively timed throughout their visit to clinics, before implementation of a hospital system-wide EMR system and then again 2 months, 6 months, and 2 years after implementation. Data were analyzed to investigate the effects of EMR implementation on labor cost and provider time. Results: Total labor costs per patient visit significantly increased at 2 months after EMR implementation (from 36.88 to 46.04; p = 0.05). Drivers of this change included increases in the amount of time that attending surgeons spent per patient (from 9.38 to 10.97 minutes, with the cost increasing from 21.10 to 27.01), as well as increased time that certified medical assistants spent assessing patients (from 3.4 to 9.1 minutes; p < 0.001). Two months after EMR implementation, providers were spending more than twice as long documenting patient encounters (7.6 compared with 3.3 minutes; p < 0.001). However, by 6 months after implementation, total labor costs were similar to those before implementation (38.75 compared with 36.88; p = 0.689) and they remained similar at 2 years after implementation (36.88 compared with 37.73; p = 0.84). After the initial learning period following EMR implementation, providers spent more time documenting encounters (8.43 compared with 3.28 minutes; p < 0.001) but less time interacting with patients (10.03 compared with 14.65 minutes; p = 0.013). Conclusions: Using TD-ABC, we observed the EMR implementation learning period, returning to pre-introduction efficiency at 6 months. Cost increases because of increased certified medical assistant time spent with patients and physician time on documentation were offset by less patient-physician interaction. Health-care systems and policymakers should be aware that the length of the implementation period is approximately 6 months and that implementation may alter the time that providers spend with patients. Clinical Relevance: This article offers insight into the impact of EMR implementation on the orthopaedic surgeon's clinic efficiency and workflows.